Bias, Belief, and Conviction in an Age of Fake Facts - Finger, Anke; Wagner, Manuela (Routledge Research in Cultural and Media Studies, 2023)
In this book, authors engage in an interdisciplinary discourse of theory and practice on the concept of personal conviction, addressing the variety of grey zones that mark the concept. Bias, Belief, and Conviction in an Age of Fake Facts discusses where our convictions come from and whether we are aware of them, why they compel us to certain actions, and whether we can change our convictions when presented with opposing evidence that prove our personal convictions ""wrong"". Scholars from Philosophy, Psychology, Comparative Literature, Media Studies, Applied Linguistics, Intercultural Communication, and Education shed light on the topic of personal conviction, crossing disciplinary boundaries and asking questions not only of importance to scholars but related to the role and possible impact of conviction in the public sphere, education, and in political and cultural discourse. By taking a critical look at personal conviction as an element of inquiry within the humanities and social sciences, this book will contribute substantially to the study of conviction as an aspect of the self we all carry within us and are called upon to examine. It will be of particular interest to scholars in communication and journalism studies, media studies, philosophy, and psychology.